Resolution of a concatenation/coalescence kerfuffle: partitioned coalescence support and a robust family‐level tree for Mammalia. (16th August 2016) - Gatesy, John; Meredith, Robert W.; Janecka, Jan E.; Simmons, Mark P.; Murphy, William J.; Springer, Mark S.
Abstract: Recent phylogenetic analyses of a large dataset for mammalian families (169 taxa, 26 loci) portray contrasting results. Supermatrix (concatenation) methods support a generally robust tree with only a few inconsistently resolved polytomies, whereas MP‐EST coalescence analysis of the same dataset yields a weakly supported tree that conflicts with many traditionally recognized clades. Here, we evaluate this discrepancy via improved coalescence analyses with reference to the rich history of phylogenetic studies on mammals. This integration clearly demonstrates that both supermatrix and coalescence analyses of just 26 loci yield a congruent, well‐supported phylogenetic hypothesis for Mammalia. Discrepancies between published studies are explained by implementation of overly simple DNA substitution models, inadequate tree‐search routines and limitations of the MP‐EST method. We develop a simple measure, partitioned coalescence support (PCS), which summarizes the distribution of support and conflict among gene trees for a given clade. Extremely high PCS scores for outlier gene trees at two nodes in the mammalian tree indicate a troubling bias in the MP‐EST method. We conclude that in this age of phylogenomics, a solid understanding of systematics fundamentals, choice of valid methodology and a broad knowledge of a clade's taxonomic history are still required to yield coherent phylogenetic inferences.